The importance of reliable monitoring methods for the management of small, isolated populations. Issue 7 (22nd May 2020) - Elliot, Nicholas B.; Bett, Alice; Chege, Monica; Sankan, Kasaine; de Souza, Nadia; Kariuki, Linus; Broekhuis, Femke; Omondi, Patrick; Ngene, Shadrack; Gopalaswamy, Arjun M.
Abstract: To effectively manage wildlife populations, it is essential to reliably estimate their abundance. This is particularly the case for small, isolated populations, which are vulnerable to extirpation. Lake Nakuru National Park in Kenya is one such small, isolated area where an introduced population of African lions ( Panthera leo ) is vulnerable to genetic degradation and catastrophic events. A founder population of six individuals was introduced between 1984 and 1992, with no further recorded immigration. We used Bayesian spatially‐explicit capture–recapture models to estimate lion density and abundance based on unstructured spatial sampling. For individuals over the age of 1 year, posterior mean lion density was estimated to be 6.75 (mode = 5.93, posterior SD = 0.92) individuals/100 km 2, with a mean abundance of 11.37 (mode = 10, posterior SD = 1.54), and a sex ratio of 1.38♀:1♂. Previous reports provided abundance figures much higher than ours. However, our estimates are the result of the first scientifically robust survey and we discuss why they should be viewed as a baseline rather than being suggestive of population decline, and how the discrepancy highlights the need for regular systematic surveys using a standardized framework. Given the small population size and prolonged genetic isolation, we provide long‐term management recommendations to secure this lion population.